Cutting force and vibration prediction of milling processes regarding the nonlinear behavior of cascade controlled feed drives - Ju, Shu; Gross, Daniel; Hanenkamp, Nico (Production Engineering, 2022)
Milling processes are characterized by their high degree of flexibility regarding shape creation and thus occur in many value adding processes in the electrical and mechanical engineering industry. To facilitate the systematic prediction and the efficient optimization of the process performance, a holistic simulation model of the milling process with cascade controlled feed drives is developed. The integrated model consists of two subsystems, namely the feed drive model and the process model. In the feed drive model, the dynamic models of the electric motors, the serially connected torsional oscillators of the mechanical elements and the cascade control system are established. In this model, the coordinate point of the milling tool is computed at each discrete time step and assigned to the process model. The cutting forces and the corresponding load torques are calculated in the process model and sent back to the feed drive model. In addition, practical validation of the complete system has been conducted both in the time and the frequency domain. The simulation results yield an accurate prediction of the tooth passing frequency with a variance of less than 1%. Moreover, the influence of the cascade control parameters and the nonlinear behavior of the electric motor on the process vibrations have been experimentally verified.<br
Keywords: Milling process simulation; Cascade control model; Cutting force prediction; Vibration prediction